A qualitative study exploring the experiences and perceptions of patients with rheumatoid arthritis before and after wearing foot orthoses for 6 months. - Ramos-Petersen, Laura; Nester, Christopher; Ortega-Ávila, Ana Belén; Skidmore, Sue; Gijón-Noguerón, Gabriel (My University, 2021)
Foot pathology in people with rheumatoid arthritis (RA) can have a psychosocial impact, but interventions such as foot orthoses can reduce foot pain, improving physical activity and quality of life. A previous meta-analysis concluded that foot orthoses can relieve pain and disability and enhance patient's well-being. The aim of this study was to explore the experiences of people with RA, before and after wearing foot orthoses for 6 months. Data were collected through digital recordings of semi-structured interviews carried out before and after wearing foot orthoses for 6 months. A thematic analysis of the transcripts was used to identify themes. Six female participants with RA wore foot orthoses for 6 months in Spain. The mean disease duration was more than 10 years. The findings showed three key themes emerged from the data: (1) improvement in physical activity; (2) footwear… a tricky situation and (3) social implications of RA feet. It is concluded that patients reported that wearing foot orthoses can have a positive impact on physical activity and improve general wellness and quality of life. However, to achieve the potential positive benefits, people with RA also needed to wear suitable footwear (defined as footwear which accommodates both the foot and the insole while maintaining the fit and function of the shoe). Despite the positive impact of wearing orthoses, participants stated that complexities of finding suitable footwear acted as a blocker.
https://openpolicyfinder.jisc.ac.uk/id/publication/7008
Keywords: Artritis reumatoide; Pies; Ortopedia; Qualitative; Experiences; Perceptions; Rheumatoid artrhitis; Foot orthoses